Inklusivitas Perekonomian di Kabupaten Hulu Sungai Utara Tahun 2022: Pendekatan Model Miyazawa - Murjani, Ahmadi; Rifani, Akhmad; Ramadhan, Muhammad Febrian Rizky (Ecoplan, 2024)
One of the goals and missions of achieving sustainable development is implementing economic development that adheres to the principle of inclusivity. Therefore, policymakers in a region must identify whether the economic development undertaken is already inclusive. Following these results, it is essential for policymakers to also conduct evaluations to determine the effectiveness of the policies made in realizing inclusive economic development. These two aspects can be addressed by applying the Miyazawa Input-Output Table. Meanwhile, over the past three years, Hulu Sungai Utara Regency has experienced a range of economic and social phenomena that necessitate further study of economic inclusivity. As a result of these conditions, the Regency has been selected as the locus for this research. The findings on the economic inclusivity in this Regency are expected to serve as a reference for policy in developing the economy of Hulu Sungai Utara. Based on the results, it is known that the economy in Hulu Sungai Utara Regency has not yet been fully inclusive. Investments in sector code E (Water Supply, Waste Management, Waste, and Recycling), sector code A (Agriculture, Forestry, and Fishery), sector code C (Manufacturing Industry), and sector code J (Information and Communication) have the potential to increase the welfare of low-income communities, which would then yield an inclusive economic development in the area.